Matching of oligoclonal immunoglobulin transcriptomes and proteomes of cerebrospinal fluid in multiple sclerosis - Obermeier, Birgit; Mentele, Reinhard; Malotka, Joachim; Kellermann, Josef; Kümpfel, Tania; Wekerle, Hartmut; Lottspeich, Friedrich; Hohlfeld, Reinhard; Dornmair, Klaus (Nature medicine, 2008)
We describe a method for correlating the immunoglobulin (Ig) proteomes with the B cell transcriptomes in human fluid and tissue samples, using multiple sclerosis as a paradigm. Oligoclonal Ig bands and elevated numbers of clonally expanded B cells in the cerebrospinal fluid (CSF) are diagnostic hallmarks of multiple sclerosis. Here we compared the Ig transcriptomes of B cells with the corresponding Ig proteomes in CSF samples from four subjects with multiple sclerosis. We created individual Ig transcriptome databases that contained the subject-specific mutations introduced by V(D)J recombination and somatic hypermutation and then searched the CSF for corresponding characteristic peptides by mass spectrometry. In each sample, the Ig transcriptomes and proteomes strongly overlapped, showing that CSF B cells indeed produce the oligoclonal Ig bands. This approach can be applied to other organ-specific diagnostic fluid or tissue samples to compare the Ig transcripts of local B cells with the corresponding antibody proteomes of individual subjects.